Building Integrated Photovoltaic (BIPV): Implementing Artificial Intelligent (AI) on Designing Rooftile Photovoltaic - Syahyadi, Rizal; Safitri, Nelly; Widia, Riza; Safriadi; Azwar (International Journal of Data Science, 2023)
The monocrystalline photovoltaic (PV) is integrating into the natural clay used to fabric the terracotta rooftile. The enlargement of the rooftile’s dimension increased the power output of the PVs. This paper describes briefly the technology of building integrated photovoltaic (BIPV) development and integration to buildings and houses, especially by using artificial intelligent (AI) while composing and designing the terracotta rooftile PV. The examination of property’s parameter namely dimensions of the terracotta rooftile PVs on top of the house, the voltage, current, power, and efficiency of the PVs themselves were also considered. As the examination run, we also compare the results to the convenient mounted rooftop PV. The results showed that the output power of the PV reached its maximum power as the dimension of the terracotta rooftile PVs enlarge to fully cover the roof.